The respiratory health effects of acute in vivo diesel and biodiesel exhaust in a mouse model - Landwehr, Katherine; Mead-Hunter, Ryan; O'Leary, R.A.; Kicic, Anthony; Mullins, Ben; Larcombe, Alexander (2024)
Background: Biodiesel, a renewable diesel fuel that can be created from almost any natural fat or oil, is promoted as a greener and healthier alternative to commercial mineral diesel without the supporting experimental data to back these claims. The aim of this research was to assess the health effects of acute exposure to two types of biodiesel exhaust, or mineral diesel exhaust or air as a control in mice. Male BALB/c mice were exposed for 2-hrs to diluted exhaust obtained from a diesel engine running on mineral diesel, Tallow biodiesel or Canola biodiesel. A room air exposure group was used as a control. Twenty-four hours after exposure, a variety of respiratory related end point measurements were assessed, including lung function, responsiveness to methacholine and airway and systemic immune responses. Results: Tallow biodiesel exhaust exposure resulted in the greatest number of significant effects compared to Air controls, including increased airway hyperresponsiveness (178.1 ± 31.3% increase from saline for Tallow biodiesel exhaust exposed mice compared to 155.8 ± 19.1 for Air control), increased airway inflammation (63463 ± 13497 cells/mL in the bronchoalveolar lavage of Tallow biodiesel exhaust exposed mice compared to 40561 ± 11800 for Air exposed controls) and indications of immune dysregulation. In contrast, exposure to Canola biodiesel exhaust resulted in fewer significant effects compared to Air controls with a slight increase in airway resistance at functional residual capacity and indications of immune dysregulation. Exposure to mineral diesel exhaust resulted in significant effects between that of the two biodiesels with increased airway hyperresponsiveness and indications of immune dysregulation. Conclusion: These data show that a single, brief exposure to biodiesel exhaust can result in negative health impacts in a mouse model, and that the biological effects of exposure change depending on the feedstock used to make the biodiesel.